Lactobacillus plantarum L15 Alleviates Colitis by Inhibiting LPS-Mediated NF-κB Activation and Ameliorates DSS-Induced Gut Microbiota Dysbiosis - Yu, Peng; Ke, Chuxin; Guo, Jiaxin; Zhang, Xiuling; Li, Bailiang (Frontiers in Immunology, 2020)
Previous studies have suggested that the Lactobacillus plantarum bacteria strain could be effective in ulcerative colitis (UC) management. However, its effects are strain-specific and the related mechanisms for its attenuating effects on UC remain unclear. This study aimed to elucidate the underlying mechanisms for the protective effect of L. plantarum on UC. Firstly, 15 L. plantarum strains were screened for potential probiotic characteristics with good tolerance to simulated human gastrointestinal transit and adhesion. Secondly, the inflammatory response of selected strains to the Caco-2 cells induced by lipopolysaccharide (LPS) was measured. Finally, an in vivo mouse model induced by dextran sulfate sodium (DSS) was used to assess the beneficial effects and likely action mechanisms the successfully screened in vitro strain, L. plantarum L15. In vitro results showed that L. plantarum L15 possessed the highest gastrointestinal transit tolerance, adhesion and reduction of pro-inflammatory abilities compared to the other screened strains. In vivo, high dose of L. plantarum L15 supplementation increased the body weight, colon length and anti-inflammatory cytokine production. Pro-inflammatory cytokine production, disease activity index (DAI) levels and myeloperoxidase (MPO) parameters decreased using this strain. In addition, L. plantarum L15 alleviated the histopathological changes in colon, modulated the gut microbiota and decreased LPS secretion. The activities of this strain down-regulated the expression of TLR4 and MyD88 genes as well as genes associated with NF-κB signaling pathway. Our findings present L. plantarum L15 as a new probiotic, with promising application for UC management.